Upaya Pengembangan Kualitas Literasi dan Numerasi Siswa SD Negeri 060839 - Sinaga, Binsar Martua Valentino; Nasution, Faiz Albar (Yayasan Literasi Sains Indonesia, 2023)
Literacy is a manifestation of real skills, which are specifically the cognitive skills of reading and writing, which are independent of your context, where the skills were obtained from whom and how they were obtained. Meanwhile, according to numeracy, it is the ability to apply number concepts and calculation operation skills in everyday life, for example at home, work in community life, and the ability to explain information found around us.This study aims to develop the literacy and numeracy quality of SD Negeri 060839 students. In carrying out its development efforts it is applied the Group Work intervention method to deal with problems that exist in SD Negeri 060839 students. In carrying out its activities the methods used are preparation, intake and contracts, assessment, planning and intervention. Based on the trials conducted, it showed significant changes in the literacy and numeracy of SD Negeri 060839 students by implementing literacy activities for 15 minutes by implementing these activities every day. While the numeracy activities are followed by relying on the students' memory in reciting so that they can easily apply these activities in their daily lives.